Characterization of biomaterials intended for use in the nucleus pulposus of degenerated intervertebral discs. (15th September 2020) - Schmitz, Tara C.; Salzer, Elias; Crispim, João F.; Fabra, Georgina Targa; LeVisage, Catherine; Pandit, Abhay; Tryfonidou, Marianna; Maitre, Christine Le; Ito, Keita
Abstract: Biomaterials for regeneration of the intervertebral disc must meet complex requirements conforming to biological, mechanical and clinical demands. Currently no consensus on their characterization exists. It is crucial to identify parameters and their method of characterization for accurate assessment of their potential efficacy, keeping in mind the translation towards clinical application. This review systematically analyses the characterization techniques of biomaterial systems that have been used for nucleus pulposus (NP) restoration and regeneration. Substantial differences in the approach towards assessment became evident, hindering comparisons between different materials with respect to their suitability for NP restoration and regeneration. We have analysed the current approaches and identified parameters necessary for adequate biomaterial characterization, with the clinical goal of functional restoration and biological regeneration of the NP in mind. Further, we provide guidelines and goals for their measurement. Statement of significance: Biomaterials intended for restoration of regeneration of the nucleus pulposus within the intervertebral disc must meet biological, biomechanical and clinical demands. Many materials have been investigated, but a lack of consensus on which parameters to evaluate leads to difficulties in comparing materials as well as mostly partial characterization of the materials in question. A gap between current methodology and clinically relevant and meaningful characterization is prevalent. In this article, we identify necessary methods and their implementation for complete biomaterial characterization in the context of clinical applicability. This will allow for a more unified approach to NP-biomaterials research within the field as a whole and enable comparative analysis of novel materials yet to be developed. Graphical Abstract: Image, graphical abstract